The Relation of the Role of the Generation Planning Ambassador (Genre) with the Knowledge Level of Reproductive Health in Medan City Adolescents - Putra, Yobel (Journal of Sumatera Sociological Indicators, 2022)
This study examines the influence of the Planning Generation Ambassador (Genre) on Adolescent Reproductive Health Knowledge in Medan City. This research was carried out at the Youth Counseling Information Center (PIK-R) group in Medan City, namely the PIK-R Syahadah UMSU Group, PIK-R AN-Nahlu MAN 1 Medan and PMR Wira Sultan Iskandar Muda Medan. The theory used is the socialization theory proposed by Peter L. The method used in this research is quantitative research methods. With nonprobability sampling technique in the form of saturated sampling as many as 79 from the three PIK-R groups. The independent variable in this study is the Planning Generation Ambassador which includes one indicator, namely the socialization given to teenagers in Medan City. While the dependent variable (dependent) is knowledge of reproductive health which includes three indicators, namely: knowledge of reproductive health, understanding reproductive health, and carrying out reproductive health activities (Notoatmojo, 2012). The method used in this research is quantitative research methods. With nonprobability sampling technique in the form of saturated sampling as many as 79 from the three PIK-R groups. The independent variable in this study is the Planning Generation Ambassador which includes one indicator, namely the socialization given to teenagers in Medan City